Nightmares! : Nightmares! #1 - Segel, Jason, 1979-; Miller, Kirsten, 1973-; Kwasny, Karl (New York : Delacorte Books for Young Readers, 2014)
"Twelve-year-old Charlie and his friends must stop nightmares from taking over their town before it's too late"--
Keywords: Nightmares -- Fiction